Distance Measurement on an Endogenous Membrane Transporter in E. coli Cells and Native Membranes Using EPR Spectroscopy1. (31st March 2015) - Joseph, Benesh; Sikora, Arthur; Bordignon, Enrica; Jeschke, Gunnar; Cafiso, David S.; Prisner, Thomas F.
Abstract Membrane proteins may be influenced by the environment, and they may be unstable in detergents or fail to crystallize. As a result, approaches to characterize structures in a native environment are highly desirable. Here, we report a novel general strategy for precise distance measurements on outer membrane proteins in whole Escherichia coli cells and isolated outer membranes. The cobalamin transporter BtuB was overexpressed and spin‐labeled in whole cells and outer membranes and interspin distances were measured to a spin‐labeled cobalamin using pulse EPR spectroscopy. A comparative analysis of the data reveals a similar interspin distance between whole cells, outer membranes, and synthetic vesicles. This approach provides an elegant way to study conformational changes or protein–protein/ligand interactions at surface‐exposed sites of membrane protein complexes in whole cells and native membranes, and provides a method to validate outer membrane protein structures in their native environment.